Ethnobotany of Adenium obesum (Forssk.) Roem. &Schult. : A Review - Setiyanto, Afif Eka Rahma; Zulfatim, Heni Sukma; Septi Tri Puspita Sari; Krisnawati, Dewi (Biotropika: Journal of Tropical Biology, 2024)
Adenium obesum (Forssk.) Roem. & Schult., commonly known as the ‘desert rose,’ is a member of the Apocynaceae family, cultivated extensively in various tropical regions. While Adenium obesum is primarily used as an ornamental plant, previous research has documented its biological activities and phytochemical constituents. However, there has been no comprehensive review of its ethnobotanical applications. This study aims to summarize and discuss the ethnobotanical uses of Adenium obesum through a literature review. The ethnobotanical information of Adenium obesum can be categorized into five primary groups: ornamental plant, eco-print source, religious ceremonies, medicinal uses, and toxic effects. The plant is renowned for its aesthetic appeal, particularly its flowers and roots, often shaped into bonsai. This characteristic underscores its potential in the floriculture industry and agrotourism. In eco-printing, Adenium obesum creates patterns on fabrics through direct contact. In religious contexts, the plant is used in offerings and pilgrimage ceremonies at cemeteries. Adenium obesum has been approved for treating various diseases in humans and chickens. Conversely, it also possesses toxic properties that are harnessed for hunting purposes. Different regions and cultures employ Adenium obesum in diverse ethnobotanical applications. The findings conclude that Adenium obesum has significant ethnobotanical utility, presenting several prospects, such as its incorporation into the ornamental plant industry, agrotourism, and the development of other art objects or plant parts beyond its flowers. Furthermore, scientific validation is necessary to maximize the beneficial effects and manage the toxic properties of this plant to ensure its proper utilization.